O doświadczeniu śmierci - Stróżewski, Władysław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2012)
The main goal of this article is to present death as portrayed in literature and especially in poetry (Rilke, Leśmian, Norwid). The author presents poetry and philosophy dealing with death experiences as well as other people’s death. This article describes certain traumatic human emotions which accompany an experience of death.